Genotypic and Phylogenetic Profiling of Biofilm-Forming Staphylococcus Isolates Recovered from Device-Associated Chronic Infections: A Case–Control Study from Northern India - Naveed, Danish; Ghafoori, Rabiullah; Zakarya, Ahmad; Tariq, Rabail; Khan, Afsheen; Shoukat, Mamoona; Fatima, Zaira (Journal of Neonatal Surgery, 2025)
Background: To determine the frequency of aortic arch types and branching pattern variations in a cohort of patients and assess their surgical relevance. Methods: This descriptive cross-sectional study included 72 patients who underwent computed tomography angiography (CTA) or surgical exploration between June 2023 and June 2024. Arch types (I–III) and branching patterns (classic three-branch, bovine arch, aberrant right subclavian artery, vertebral origin variants, right-sided arch) were classified. Surgical outcomes including operative time, intraoperative adjustments, and complications were analyzed. Results: Type I arch was most frequent (63.9%), followed by Type II (23.6%) and Type III (12.5%). Classic branching pattern was seen in 62.5% of participants, while 37.5% had variations, most commonly bovine arch (20.8%). Patients with variant branching had significantly longer mean operative time (215 ± 30 min vs. 188 ± 25 min, p = 0.03) and required more intraoperative adjustments (p = 0.04), though rates of stroke and 30-day mortality were not significantly different. Conclusion: Aortic arch variations are relatively common and have measurable effects on surgical complexity. Preoperative imaging and individualized planning are critical to reducing operative challenges and optimizing outcomes.